UNIVERSAL EMBEDDED RECONFIGURABLE HARDWARE PLATFORM FOR MULTIMEDIA APPLICATIONS IN REAL-TIME - Livshitz, Michael; Petrovsky, Alexey; Stankevich, Andrey; Kachinsky, Mikhail; Petrovsky, Alexander (International Journal of Computing, 2014)
This paper deals with reconfigurable hardware platform for different purposes real-time speech and audio signal processing. A design conception and turnkey solution are described. Much attention is paid to reconfigurable peripheral processor meant for external interface realization, pre- and post- data processing as well as digital signal processing algorithms implementation with the object of the DSP unloads. Moreover, three applications implemented on the considered platform are demonstrated.